Chronic impacts of natural infrastructure on the physical and psychological health of university students during and after COVID−19: a case study of Chengdu, China - Peng, Yi; He, Haoxing; Lv, Bingyang; Wang, Jiali; Qin, Qiao; Song, Jialu; Liu, Yuzhou; Su, Wenjun; Song, Huixing; Chen, Qibing (Frontiers in Public Health, 2024)
IntroductionThe COVID-19 pandemic has underscored the health benefits of green spaces, yet research on how specific elements of natural infrastructure affect well-being during the pandemic has been limited.MethodsThis study, conducted at Sichuan Agricultural University with 300 students in 2022, investigated how urban natural infrastructure impacts physical and psychological well-being during the pandemic. Different aspects of natural infrastructure, such as thermal comfort, air quality (negative ion concentration), and noise and light levels, varied in their positive effects on students’ health.ResultsThe findings revealed that 65.6% of university students felt reduced stress when engaging with outdoor spaces, and 72.8% of them renewed recognized the therapeutic value of nature.DiscussionThe study emphasizes the importance of incorporating natural elements into urban planning to enhance outdoor activity and well-being, especially in post-pandemic settings. Recommendations are provided for future urban design to address the therapeutic needs of specific populations.